2014
DOI: 10.1177/2325967113519741
|View full text |Cite
|
Sign up to set email alerts
|

Knee Injuries in Downhill Skiers

Abstract: Background:Knee injuries account for approximately one third of injuries in skiers. Researchers have proposed several mechanisms of knee injury in skiers. However, the frequencies of these mechanisms have varied in different studies.Purpose:To identify the most common knee injury mechanisms in recreational downhill skiers and to assess injury frequencies across several demographics.Study Design:Descriptive epidemiology study.Methods:Over 6 ski seasons, 541 patients with acute knee injuries completed a survey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
37
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 35 publications
6
37
0
5
Order By: Relevance
“…In accordance with other studies, the most common type of self-reported fall among knee injured skiers seems forward falling with body rotation (‘valgus external rotation’) 14 18 19. The larger amount of reported binding release among forward falls with and without body rotation becomes plausible because current bindings are mostly designed to release during a simple forward fall (upward release function of the heel piece) or during a forward fall with body rotation (side release function of the toe piece of the ski binding) 20.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with other studies, the most common type of self-reported fall among knee injured skiers seems forward falling with body rotation (‘valgus external rotation’) 14 18 19. The larger amount of reported binding release among forward falls with and without body rotation becomes plausible because current bindings are mostly designed to release during a simple forward fall (upward release function of the heel piece) or during a forward fall with body rotation (side release function of the toe piece of the ski binding) 20.…”
Section: Discussionsupporting
confidence: 91%
“…Erkeklerde (%60.4) kadınlara (%39.6) göre %20.8 oranında daha fazla yaralanma görüldüğü belirlendi. Bilimsel çalışmalarda sporcu veya rekreasyonel kayakçılarda yaralanma ve sakatlık vakalarının erkeklerde kadınlara göre daha fazla olduğu belirtilmiştir (10,11,14,21 (14). Costa--Score ve ark.…”
Section: Discussionunclassified
“…Daha önceki bi--limsel çalışmalarda da kayak nedenli yara--lanmaların %50'den fazlasının alt ekstre--mitede, daha sonra ise üst ekstremitede olduğu bildirilmiştir (10,11,14,15). Özel--likle kayak yaparken kayağın, boardun veya kızağın kontrolünde yer alan alt ekstremite daha fazla fiziksel strese ma--ruz kaldığı için, bu bölgede yaralanma oranı da daha fazladır (18).…”
Section: Discussionunclassified
See 2 more Smart Citations